2021
DOI: 10.1002/sej.1403
|View full text |Cite
|
Sign up to set email alerts
|

High‐performer mobility to entrepreneurship and parent‐firm performance

Abstract: Research Summary: We investigate the effect of highperformer employee mobility to same-industry startups on parent-firm performance. High-performer mobility induces a loss of human assets but might also enable competition by transferring human and complementary assets from the parent firm to a competitor. Only when such transfer occurs is mobility to same-industry startups more harmful than other types of high-performer mobility. Human and complementary asset transfer is conditional on the departing high perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Gjerlø‐Juel and Dahl (2021) find that employee ability to accumulate and a recipient firm's ability to absorb human and other complementary assets lower prior employer performance. Based on their study, employee tenure as a proxy for accumulation of human and complementary assets, and the size of the startup as a proxy for knowledge absorption are added considerations for future research in studying the effects of IDD.…”
Section: Discussionmentioning
confidence: 99%
“…Gjerlø‐Juel and Dahl (2021) find that employee ability to accumulate and a recipient firm's ability to absorb human and other complementary assets lower prior employer performance. Based on their study, employee tenure as a proxy for accumulation of human and complementary assets, and the size of the startup as a proxy for knowledge absorption are added considerations for future research in studying the effects of IDD.…”
Section: Discussionmentioning
confidence: 99%
“…Literature [22] constructed a correlation model between corporate entrepreneurship and performance based on social psychology, through which it can effectively promote the enhancement of corporate entrepreneurial behavior. Literature [23] analyzed the correlation between employee mobility and parent company performance, and high-performance employee mobility can improve the entrepreneurial performance of startups, which in turn helps startups better accumulate industry experience. Literature [24] analyzed data from entrepreneurial interviews with 57 students, and university entrepreneurship training can help students gain better access to forms of human capital that can help students improve their entrepreneurial potential and enhance scalable entrepreneurial performance.…”
Section: ) Entrepreneurial Performancementioning
confidence: 99%
“…This fear of spinouts may cause parents to underinvest in their internal ventures (Burke & To, 2001). More recently, Gjerlø-Juel and Dahl (2021) found that the tenure of employee entrepreneurs and the initial size of their spinouts have crucial impact on the parents. In order to negatively impact parents through competition, spinouts need to be able to transfer accumulated knowledge from parents and absorb it into the new venture.…”
Section: 4mentioning
confidence: 99%